Dead or Alive: Racial Finance and the Corpse‐Value of the African American Slave Body. Issue 1 (21st February 2020) - Bride, Amy
Abstract: Based on the work completed during a research placement at the Library of Congress studying manuscripts held within the Black History Collection, the paper explores how studying the financial mechanics of the slave trade – from insurance to speculation, asset stripping to securities – reveal a horrific turning point in the history of slavery in which the black body became more valuable dead than alive. Not only did this turning point work to 'legitimize' the murder of African Americans, it also demonstrates how both physical and financial racial violence during the domestic slave trade has a direct relationship to the deregulation of the slave market and the subsequent corpse‐valuation of the slave body.